Examining the Development of Internet Finance Based on a Comprehensive Index Analysis - Weiwei, Pu; Maelah, Ruhanita (Journal of Ecohumanism, 2024)
This study aims to analyze the development status of Internet finance in China from four aspects: P2P lending, crowdfunding, third-party payment, and big data. The Internet finance industry development index is a comprehensive indicator used to quantitatively analyze the overall development of the Internet finance industry. The data was sourced from representatives of Internet finance companies and third-party organizations. A model based on data from 2010 to 2019 was constructed to obtain the development index of Internet finance and its sub-sectors. The weight determination process was carried out through pairwise comparisons among the factors and expert scoring. The results show that Internet finance in China has experienced significant growth since 2014, particularly in the P2P lending sector. Third-party payment has become increasingly important in China's payment system, while crowdfunding and big data have also expanded and developed rapidly, although their overall impact on the financial industry remains relatively small. Overall, the development of Internet finance offers numerous benefits but also presents risks that warrant regulatory attention.